2014
DOI: 10.1097/ico.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Diabetes and Keratoconus

Abstract: The results of this study suggest that DM provides a statistically significant protective effect against the development of KC. This investigation showed that the biomechanical effects of cross-linking were also reflected in epidemiological results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 17 publications
0
26
0
4
Order By: Relevance
“…A higher hysteresis suggests a more rigid and less deformable cornea. Seven cross-sectional clinic-based studies in Western Europe, 87, 90, 91, 92 United States, 93 Brazil, 89 Israel 88 and Iran 94 have found type 1 and type 2 DM participants to have higher hysteresis, whereas only one study (Turkish study) 95 found them to have a lower hysteresis, compared with age-matched controls. In one study, it was found that the fasting blood glucose level was significantly but weakly correlated ( r =0.28) to the corneal hysteresis.…”
Section: Cornea Stroma and Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher hysteresis suggests a more rigid and less deformable cornea. Seven cross-sectional clinic-based studies in Western Europe, 87, 90, 91, 92 United States, 93 Brazil, 89 Israel 88 and Iran 94 have found type 1 and type 2 DM participants to have higher hysteresis, whereas only one study (Turkish study) 95 found them to have a lower hysteresis, compared with age-matched controls. In one study, it was found that the fasting blood glucose level was significantly but weakly correlated ( r =0.28) to the corneal hysteresis.…”
Section: Cornea Stroma and Biomechanicsmentioning
confidence: 99%
“…104 Unfortunately, the published cross-sectional studies did not demonstrate a consistent association between DM and such alteration of corneal shapes. 93, 94 …”
Section: Cornea Stroma and Biomechanicsmentioning
confidence: 99%
“…58 The biomechanical theory of KCN postulates that elevated glucose in patients with DM leads to glycosylation of corneal fibers, which causes collagen crosslinking and strengthens the cornea thus reducing the risk of developing ectasia and KCN. 912 While some clinical evidence supports this theory, 5,6 a recent case-control study of 1377 patients with KCN actually found that patients with DM were more likely to have KCN compared to controls.…”
mentioning
confidence: 99%
“…Although they concluded that diabetes mellitus (DM) provides a statistically significant protective effect against the development of keratoconus (KC), the link between DM and KC is still not clear. [1][2][3] We found it interesting that the age range of their consecutive patients was 18 to 48 years in the KC group, although there were no stated exclusion criteria based on age. 1 Did the authors look at the association between DM and KC by specific age groups as was done by Seiler et al 2 ?…”
Section: To the Editormentioning
confidence: 99%